R-R-RTR MECHANISM PATHS - Iulian POPESCU; Liliana LUCA (Fiabilitate şi Durabilitate)
Let’s consider a mechanism with two conducting elements and a RTR dyad and the paths of a point onthe connecting rod with variable length are determined. Let’s consider the movements of the conductingelements correlated through linear relations. There are cases analysed when movement is intermittent or when aconducting element performs more rotations than the other